1965
DOI: 10.1098/rspb.1965.0069
|View full text |Cite
|
Sign up to set email alerts
|

The maintenance energy of bacteria in growing cultures

Abstract: The variation, with growth rate, of the yield of organism from the substrate used as energy source is attributed to consumption of energy at a constant rate for cell maintenance. From the laws of growth, a simple relation between the maintenance requirement, the growth yield and the growth rate is derived. The relation is shown to be in good agreement with the available data. A distinction is made between ‘observed’ yield and ‘true’ yield of organisms. Values for maintenance energies and ‘true growth yields’ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
238
0
6

Year Published

1974
1974
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,190 publications
(252 citation statements)
references
References 0 publications
8
238
0
6
Order By: Relevance
“…Its evaluation is obtained by adding to the base ATP yield of 41.25 mmol ATP/g-biomass for growth the total maintenance fluxes over all modes divided by the total growth rate from all the growth modes. 4,29 Y ATP=B ¼ overall ATP consumption rate by growthðr 23 Þand maintenanceðr 22 Þ biomass formation rate…”
Section: More Detailed Networkmentioning
confidence: 99%
“…Its evaluation is obtained by adding to the base ATP yield of 41.25 mmol ATP/g-biomass for growth the total maintenance fluxes over all modes divided by the total growth rate from all the growth modes. 4,29 Y ATP=B ¼ overall ATP consumption rate by growthðr 23 Þand maintenanceðr 22 Þ biomass formation rate…”
Section: More Detailed Networkmentioning
confidence: 99%
“…If the maintenance energy (Pirt 1965) is known, the experimental Y~,~, can be calculated according to:…”
Section: Atp Requirement For Anaerobic Chemostat Growth Of S Cerevismentioning
confidence: 99%
“…Moss et al [17] showed that when the glucose concentration for cell mass does not always remain constant. Pirt [22] suggested that the change in the "observed" cell mass yield coefficient was due to an energy of maintenance, described as the energy or substrate consumed for functions other than t.he production of new cell material ie. growth., Such functions may be the maintenance of solute gradients, turnover of macromolecules and motion.…”
Section: Navarro and Durandmentioning
confidence: 99%